Pedagogies of the Walking Dead - Michael A. Peters; Tina Besley (Universidad Pedagógica Nacional, 2016)
This paper investigates the trope of the zombie and the recent upsurge in popular culture surrounding the figure of the zombie described as the "walking dead". We investigate this trope and figure as a means of analyzing the "pedagogy of the walking dead" with particular attention to the crisis of education in the era of neoliberal capitalism. In particular we examine the professionalization and responsibilization of teachers in the new regulative environment and ask whether there is any room left for the project of critical education.